Hydrogen as an electron donor for dechlorination of tetrachloroethene by an anaerobic mixed culture. - DiStefano, T D (1992)
Hydrogen served as an electron donor in the reductive dechlorination of tetrachloroethene to vinyl chloride and ethene over periods of 14 to 40 days in anaerobic enrichment cultures; however, sustained dechlorination for more extended periods required the addition of filtered supernatant from a methanol-fed culture. This result suggests a nutritional dependency of hydrogen-utilizing dechlorinators on the metabolic products of other organisms in the more diverse, methanol-fed system. Vancomycin, an inhibitor of cell wall synthesis in eubacteria, was found to inhibit acetogenesis when added at 100 mg/liter to both methanol-fed and hydrogen-fed cultures. The effect of vancomycin on dechlorination was more complex. Methanol could not sustain dechlorination when vancomycin inhibited acetogenesis, while hydrogen could. These results are consistent with a model in which hydrogen is the electron donor directly used for dechlorination by organisms resistant to vancomycin and with the hypothesis that the role of acetogens in methanol-fed cultures is to metabolize a portion of the methanol to hydrogen. Methanol and other substrates shown to support dechlorination in pure and mixed cultures may merely serve as precursors for the formation of an intermediate hydrogen pool. This hypothesis suggests that, for bioremediation of high levels of tetrachloroethene, electron donors that cause the production of a large hydrogen pool should be selected or methods that directly use H2 should be devised.